Ultrasound-guided pericardiocentesis: a novel parasternal approach - Osman, Adi; Tan, Wan Chuan; Ab Rahman, Jamalludin; Via, Gabriele; Tavazzi, Guido (Wolters Kluwer Health, Inc., 2018)
The aim of this study was to evaluate a novel pericardiocentesis technique using an in-plane parasternal medial-to-lateral approach with the use of a high-frequency probe in patients with cardiac tamponade. Background Echocardiography is pivotal in the diagnosis of pericardial effusion and tamponade physiology. Ultrasound guidance for pericardiocentesis is currently considered the standard of care. Several approaches have been described recently, which differ mainly on the site of puncture (subxiphoid, apical, or parasternal). Although they share the use of low-frequency probes, there is absence of complete control of needle trajectory and real-time needle visualization. An in-plane and real-time technique has only been described anecdotally. Methods and results A retrospective analysis of 11 patients (63% men, mean age: 37.7 ± 21.2 years) presenting with cardiac tamponade admitted to the tertiary-care emergency department and treated with parasternal medial-to-lateral in-plane pericardiocentesis was carried out. The underlying causes of cardiac tamponade were different among the population. All the pericardiocentesis were successfully performed in the emergency department, without complications, relieving the hemodynamic instability. The mean time taken to perform the eight-step procedure was 309± 76.4 s, with no procedure-related complications.